TREACHEROUS JOURNEY OF ADVANCED PAPILLARY THYROID CARCINOMA IN PREGNANCY - Subramanian, Seetha Devi; Mathews, Gerard Jason; En, Tan Jie; Abdullah, Noor Rafhati Adyani; Ismail, Shartiyah; Merican, Nor Shaffinaz Yusoff Azmi (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Papillary thyroid carcinoma (PTC) is the most common thyroid malignancy and generally exhibits a favourable prognosis, but it can manifest with metastasis in advanced stages. Pregnancy complicates the management of such cases particularly when radioactive iodine (I-131) therapy is indicated. CASE A 26-year-old presented in her second trimester with acute exacerbation of bronchial asthma requiring mechanical ventilation. During intubation, a 6 × 4 cm anterior neck swelling was found. A computed tomography showed diffuse heterogeneous thyroid enlargement with tracheal narrowing, cervical lymphadenopathy, and pulmonary metastasis. Thyroid function tests were normal. She underwent debulking thyroidectomy with bilateral modified radical neck dissection. Patient required a tracheostomy due to tumour invasion into the trachea. Histopathology confirmed multifocal (>5 foci) classical variant PTC with the largest nodule measuring 25 mm. The tumour showed lymphovascular invasion, regional nodal metastases, and invasion into adjacent skeletal muscle indicating an advanced stage with a high risk of recurrence as per the American Thyroid Association (ATA) risk stratification. Postoperatively, we started her on levothyroxine with a TSH target of below 0.1 mIU/L. At 33 weeks gestation, an elective lower segment caesarean section was performed. Post-delivery, cabergoline was given to suppress lactation in preparation for I-131 therapy. After consultation with nuclear medicine, I-131 therapy was scheduled at 10 weeks postpartum. Levothyroxine was withheld one month prior. CONCLUSION This case highlights the challenges of managing advanced PTC with metastasis during pregnancy. Thorough multidisciplinary planning of surgery and postpartum I-131 timing is essential to ensure a seamless delivery and safety of mother and child. To safeguard breast tissue from radiation exposure, breastfeeding should be entirely discontinued at least six weeks prior to I-131 therapy. Breastfeeding should not be resumed after I-131 administration to shield the infant from radiation exposure and avert harm to the infant’s thyroid gland. Breastfeeding is not contraindicated in subsequent pregnancies.